Network Governance and Workforce Training Employability at BBPVP Makassar - Zulkifli Zulkifli; Muhammad Yunus; Nurdin Nara (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to examine how network governance explains workforce training employability at BBPVP Makassar by synthesizing regulatory, statistical, institutional, and scholarly secondary data on vocational training, labour-market transition, actor coordination, and graduate employment outcomes in South Sulawesi. Methodology: This article uses qualitative secondary data analysis. The data corpus consists of Permenaker No. 6/2025, BPS labour-market publications, BBPVP Makassar public information, OECD, ILO, and WEF reports, and peer-reviewed literature. Data were organized in Microsoft Word and Excel through document review, source triangulation, coding, and thematic synthesis. Main Findings: The secondary evidence indicates that employability is shaped by more than classroom-based training. BBPVP Makassar requires an integrated network with industry, local government, employment services, certification bodies, schools, instructors, alumni, and digital labour-market information. Coordination, trust, resource exchange, programme integration, and tracer-based performance measurement are central conditions for reducing skill mismatch and strengthening graduate transition into work. Novelty/Originality of this study: The study contributes a secondary-data-based network governance reading of vocational training in Makassar. It links labour-market indicators, vocational-training regulation, employability theory, and network governance dimensions into an analytic framework that can guide later field research, tracer studies, and policy evaluation at BBPVP Makassar.